Teaching the Rhetoric of Resistance - Samuels, R. author. aut Link
XIII, 178 p.
Keywords: Analyzes diverse contemporary reactions to the depiction of the Holocaust and other cultural traumas in museums, movies, television shows, classroom discussions, and bestselling books. This work also describes several effective pedagogical strategies dedicated to overcoming student resistances to critical analysis and social engagement.